International Trade and Devaluation of the Dollar, 1932-1934 - Cassady, Ralph; Upgren, Arthur R. (Quarterly Journal of Economics, 1936)
I. Effects of devaluation contrasted with influence of other forces, 416.— Changes in total trade following devaluation of the dollar, 417.— Relations between price and quantity changes for individual commodities, 419.— II. "Ideal" prices (compensatory solely for currency changes) contrasted with recorded prices, 423.—Classification of changes in prevailing prices, 424.— Causal factors accounting for failure of recorded prices to reflect realization of effects of devaluation, 425.— III. Conclusion, 434.